Determining and Comparing Neutron Spectra at Taiwan Photon Source before and after the Installation of Local Injection Shielding. Issue 6 (June 2020) - Lin, Yu-Chi; Chen, Ang-Yu; Sheu, Rong-Jiun
Abstract : Abstract: Accurate neutron spectrum measurements at light source facilities are difficult to perform because of relatively low and time-varying neutron intensities. A homemade Bonner cylinder spectrometer was used to determine the energy spectra of neutrons outside the lateral shielding wall of the Taiwan Photon Source before and after the installation of local injection shielding. The spectrometer, similar to the design of conventional Bonner spheres, features (1) highly sensitive neutron detection and (2) a wide-range response to neutrons with energies up to the GeV range. Neutron measurements were conducted by intentionally parking the injected 3-GeV electrons at the septum of the storage ring. On the basis of high-fidelity FLUKA simulations, neutron spectra at the measurement location under the experimental conditions were obtained and adopted as an initial guess for spectrum unfolding. The neutron spectra determined before and after the local shielding were comprehensively compared in terms of their intensities and characteristics. The local shielding resulted in overall reductions of approximately 44% and 38% in total neutron flux and dose rate, respectively. Both before and after the local shielding, high-energy neutrons (>10 MeV) were the dominant component of the radiation field, which contributed approximately 30% to 35% of the total neutron flux and 55% to 59% of the total neutron dose rate.